2019
DOI: 10.1038/s41393-019-0261-9
|View full text |Cite
|
Sign up to set email alerts
|

Health status, quality of life and socioeconomic situation of people with spinal cord injuries six years after discharge from a hospital in Bangladesh

Abstract: Study design Cross-sectional analysis of a mixed retrospective and prospective inception cohort study. Objectives To determine health status, quality of life and socioeconomic situation of people with spinal cord injuries (SCI) 6 years after discharge from a hospital in Bangladesh. Setting Bangladesh. Methods All patients alive 6 years after discharge from a hospital in Bangladesh were interviewed using the SF12 health survey, the SCI Secondary Conditions Scale, the Centre for Epidemiologic Studies Depression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 42 publications
1
10
0
1
Order By: Relevance
“…After injury, the monthly median (IQR) income of each family member was US$0 (US$0-US $18) per family member. This was sufficient to keep 9% of Our data on participants' incomes prior to injury are broadly consistent with data from our previous study of a similar cohort discharged from CRP in 2011 [26]. We found in our previous study that participants who were wheelchair dependent at discharge earnt a median (IQR) of US$65 (US $39-US$104) per month prior to injury.…”
Section: Incomesupporting
confidence: 88%
See 1 more Smart Citation
“…After injury, the monthly median (IQR) income of each family member was US$0 (US$0-US $18) per family member. This was sufficient to keep 9% of Our data on participants' incomes prior to injury are broadly consistent with data from our previous study of a similar cohort discharged from CRP in 2011 [26]. We found in our previous study that participants who were wheelchair dependent at discharge earnt a median (IQR) of US$65 (US $39-US$104) per month prior to injury.…”
Section: Incomesupporting
confidence: 88%
“…A study from Nepal found that less than half of those with an SCI had any income many years after discharge from hospital [38]. Our previous study from Bangladesh showed that only 37% of people who were wheelchair dependent on discharge from hospital were employed 2 years after discharge [3] and only 42% were employed 6 years after discharge [26]. Some evidence suggests that those who do gain employment have much lower salaries than they had prior to injury [38].…”
Section: Incomementioning
confidence: 99%
“…The secondary injury is a complex series of response including local oedema, ischemia, focal haemorrhage, oxidative stress and inflammatory responses, which occurs on the basis of the primary injury. Due to the non-regeneration of the neurons, patients often suffer from sensory disturbance as well as loss of sensation, sphincter or muscle function, which significantly declines the quality of life of patients [3]. Therefore, preventing spinal cord against traumatic or nontraumatic injury may be a hopeful method for reducing the morbidity of SCI.…”
Section: Introductionmentioning
confidence: 99%
“…In LMICs such as Bangladesh, those with SCI and their families often live in extreme poverty. We found that 65% of patients admitted to CRP in 2011 were living below the poverty line when followed up 6 years later [ 28 ], and that 91% of the families of participants in the CIVIC trial were thrown into extreme poverty by the loss of the person’s income [ 19 ]. This highlights the pressing need of these people and their families for financial assistance after injury, as was also noted in the 2013 World Health Organisation Report on SCI [ 8 ].…”
Section: Discussionmentioning
confidence: 99%